2021
DOI: 10.1177/1934578x211055345
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Activity of Novel Betulin Derivatives Containing Hydrazide-Hydrazone Moieties

Abstract: A series of novel betulin derivatives containing hydrazide-hydrazone moieties were synthesized. All compounds were evaluated for their cytotoxicity against four human carcinoma cell lines (HepG2, A549, MCF-7 and HCT-116) and a normal human gastric epithelial cell line (GES-1). Among them, compound 6i was the most potent against HepG2 and MCF-7 cell lines, with IC50 values of 9.27 and 8.87 μM, respectively. The results suggest that the incorporation of a hydrazide-hydrazone side chain at the C-28 position of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The reactions of the aldehyde group with amine derivatives were also used in the synthesis of two further series of derivatives ( Figure 16 ). In the first case, betulinic aldehyde reacted with hydrazides of various structures, obtaining derivatives containing hydrazide-hydrazone moieties 22a–i [ 80 ]. Another series of compounds, 23a–o , was created in the reaction of betulinic aldehyde hydrazone with aldehydes [ 81 ].…”
Section: Synthesis Of Betulin Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…The reactions of the aldehyde group with amine derivatives were also used in the synthesis of two further series of derivatives ( Figure 16 ). In the first case, betulinic aldehyde reacted with hydrazides of various structures, obtaining derivatives containing hydrazide-hydrazone moieties 22a–i [ 80 ]. Another series of compounds, 23a–o , was created in the reaction of betulinic aldehyde hydrazone with aldehydes [ 81 ].…”
Section: Synthesis Of Betulin Derivativesmentioning
confidence: 99%
“…Studies of the cytotoxic effect on HCT-116 cells conducted for this group of derivatives showed that the hydrazide and hydrazine derivatives containing a 4-trifluoromethylphenyl substituent ( 22d and 23h ) were the most active (IC 50 equal to 13.70 and 12.55 μM). Derivatives containing the pyridine ring 22i (IC 50 = 9.30 μM) and 23k (IC 50 = 9.32 μM) had the strongest effects on human hepatocellular carcinoma cells (HepG2) [ 79 , 80 , 81 ].…”
Section: Synthesis Of Betulin Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Various pharmacological activities were investigated by many researchers such as antimicrobial , and anticancer. , Also, hydrazide-hydrazone derivatives have been reported to have diverse pharmacological activities, especially anticancer activity. Han et al synthesized novel hydrazide-hydrazone molecules and controlled the anticancer activity on the HepG2 cell line . Anticancer activity studies of hydrazide-hydrazone molecules have been observed in many studies, and it has been determined that hydrazide-hydrazone molecules show activity against Colo-205 and HegG2 cell lines. …”
Section: Introductionmentioning
confidence: 99%